PENGARUH PENDIDIKAN PELATIHAN, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU - -, Sugiyono -; Rahadhini, MD - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
ABSTRACT The purpose of this research is to know the significance of influence of training education, motivation of work and environment of work to teachers’performance SD Negeri in unit of work Education Based Technique Unit of Gabus Subdistrict Grobogan Regency. The population is all of teachers SD Negeri in unit of work Education Based Technique Unit of Gabus Subdistrict Grobogan Regency, amount of 403 persons and sample was used is 20% or 80 persons. Technique of collecting data used questioner which has been tabulated, then conducted by validity and reliability test. The analysis used technique consist of the classic assumption test, multiple regression analysis, t test, F test and coefficient determination (R2). The result of analysis indicates that: 1) all of instruments are valid and reliable; 2) classic assumption test there was no deviation; 3) multiple regression analysis, gets equation: Y = 6,997 – 0,046X1 + 0,460X2 + 0,432X3; (4) t test of training education have p value 0,659 < 0,05; motivation of work have p value 0,000 < 0,05; and environment of work have p value 0,000 < 0,05; the conclusion is the influence of training education is unsignificant, motivation of work and environment of work are significant towards teachers’ performance; (5) F test have p value 0,000 that the correct model which used to predict the influence of training education, motivation of work, and environment of work to the teachers’ performance SD Negeri in Gabus Subdistrict Grobogan Regency; 6) R2 value is 61,4% it means training education, motivation of work, and environment of work give influence to the teachers’ performance, and the residual is influenced by other variables. Keywords: training education, work motivation, work environment, performance